Election campaign agendas, government partisanship, and the welfare state. Issue 2 (6th October 2015) - Jakobsson, Niklas; Kumlin, Staffan
Abstract : Although theoretically contentious, most empirical studies contend that electoral-political factors structure the welfare state. In practice, most studies concentrate on 'government partisanship', that is the ideological character of the government. We agree that politics matters but also seek to expand our understanding of what 'politics' should be taken to mean. Drawing on recent comparative research on agenda-setting, we study the impact of whether welfare state issues were broadly salient in the public sphere during the election campaign that produced the government. We formulate hypotheses about how such systemic campaign salience and government partisanship (separately and interactively) affect welfare generosity. We also consider how such effects might have changed, taking into account challenges to standard assumptions of representative democracy coming from the 'new politics of the welfare state' framework. We combine well-known, but updated, data on welfare state generosity and government partisanship, with original contextual data on campaign salience from 16 West European countries for the years 1980–2008. We find that campaigns matter but also that their impact has changed. During the first half of the examined period (the 1980s and early 1990s), it mainly served to facilitate government partisanship effects on the welfare state. More recently, big-time campaign attention to welfare state issues results in some retrenchment (almost) regardless of who forms the postelection government. This raises concerns about the democratic status of the politics of welfare state reform in Europe.